Comparison of the effectiveness of couple therapy based on acceptance and commitment with cognitive-behavioral couple therapy on marital conflict and cognitive flexibility in married women with marital boredom - Rafiei Saviri, Maryam; Chehri, Azita; Hosseini, Saeedeh Al-sadat; Amiri, Hassan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to compare the effectiveness of couple therapy based on acceptance and commitment with cognitive-behavioral couple therapy on marital conflict and cognitive flexibility in married women. Methods: The research was quasi-experimental with pre-test and post-test design with control group and three-month follow-up period. The statistical population included all married women with marital boredom who referred to counseling centers in Rasht in 1400, which was selected by available sampling method of 60 people and were assigned to three groups of 20 people. Data collection was performed in addition to the demographic information checklist with the Marital Boredom Questionnaire, the Marital Relationship Questionnaire and the Cognitive Flexibility Questionnaire. For the subjects of the experimental groups (both intervention programs), 12 sessions were performed, one session per week for 1 hour. In addition to descriptive statistical methods, data analysis was performed by repeated measures analysis of variance. Results: The results showed that in the post-test stage there was a significant difference between the total score of cognitive flexibility and its dimensions in the three groups (P